The Teaching of Scientific Literacy in Disadvantaged Communities (Asian Journal of Social Science Studies, 2023)
Addressing educational equality is a significant goal in many educational systems across the globe as governments aim to ensure that every citizen is scientifically literate. Scientific literacy can be understood as every citizen‟s right to consume ideas from the scientific community. In an effort to achieve scientific literacy, stakeholders in curriculum planning advocate for adaption aimed to contextualize science concepts. A case in point is when a teacher wants to engage situated cognition to teach science concepts. Sometimes this cannot be easily achieved at schools in disadvantaged communities. This is because they lack western modern science facilities that allow learners to interact with members involved in applying science concepts in their everyday cultural practices. Therefore, in an effort to ensure that learners in disadvantaged communities develop scientific literacy, this qualitative case study explored the teaching of scientific literacy in disadvantaged communities through the use of Indigenous Knowledge (IK) facilities. Data were generated through interviews, observation of community IK practices, brainstorming and teachers‟ reflections. Four Grade 11 Physical Science teachers sampled purposively participated in the study. Data collected with the use of the above tools provided answers to the research question, „Which IKS-based science pedagogies can elevate scientific literacy levels in disadvantaged communities?‟ Data were thematically analyzed and artefacts such as “mapukuta” were examined. The study found that the use of IKS based pedagogies (like mapukuta) can elevate scientific literacy levels in disadvantaged communities. The study recommended that there is a need to introduce science pedagogies which encourage scientific literacy for learners whose cultural, social, and historical encounters are not acknowledged by the curriculum; and second, more studies are required to discover how science teachers can be innovative to use out-of-school IK and integrate that with Western Science (WS) situations to address scientific literacy.